Relationship confidence in newlywed military marriages: relationship confidence partially mediates the link between attachment and communication - Hardy, Nathan R. (Kansas State University, 2012)
This study investigated the relationships between attachment style, relationship confidence, and constructive communication among a sample of 71 newlywed military couples. Using Karney & Crown’s (2007) military adapted Vulnerability-Stress-Adaptation model as a guide, the current study predicted that romantic attachment style (an enduring vulnerability) would be associated with couples’ communication (an adaptive process) directly, and indirectly through marital confidence (a marital resource). Actor and partner effects were examined using the Actor Partner Interdependence Model (APIM; Kenny, Kashy, & Cook, 2006). Results indicate that after controlling for financial worry and husband’s rank, wives’ avoidant attachment was directly associated with her constructive communication and husband’s anxious attachment was directly associated with his constructive communication. Tests of mediating paths from anxious and avoidant attachment to relationship confidence through constructive communication were significant for wives. When accounting for anxious attachment partner effects were present between relationship confidence and constructive communication. The results suggest the importance of assessing for attachment style and relationship confidence when working with military couples in the early years of their marriage.
Keywords: Marriage; Military; Communication; Attachment; Confidence; Social Psychology (0451)